High dose rate brachytherapy in nasopharyngeal carcinoma: a neglected practice - Natasha, Laishram; Mahawar, Rahul; Devi, Ningthoujam D.; Singh, Laishram J. (International Journal of Research in Medical Sciences, 2024)
Nasopharyngeal carcinomas (NPCs) are one of the most chemo- and radio- sensitive cancers of the head and neck region. It differs from other head and neck cancers in terms of signs and symptoms, treatment response and overall survival. Surgery is not the preferred treatment option, with chemoradiation being the treatment of choice, with an excellent local control rate, prognosis and overall survival. But the management of recurrent NPC is quite challenging and the treatment options available includes re-irradiation, chemotherapy, brachytherapy or surgery in rare cases. Re-irradiation in case of recurrent NPC is very difficult due to the already irradiated tissue in the radiation path, but re-irradiation with brachytherapy is an excellent treatment option for giving further doses of radiation to the nasopharynx in cases of recurrence or residual disease, by taking in consideration the already irradiated area and the radiation dose given before, and achieving a good local control rate and overall survival.